801 PRIME™ IL-15 (RPTR-147): Preliminary clinical results and biomarker analysis from a first-in-human Phase 1 study of IL-15 loaded peripherally-derived autologous T cell therapy in solid tumor patients. (9th November 2020) - Hamilton, Erika; Nikiforow, Sarah; Bardwell, Philip; McInnis, Christine; Zhang, Jeffrey; Blumenschein, George; Cristea, Mihaela; Osman, Keren; Shields, Anthony; Motta, Marlyane; Bilic, Sanela; Schoenborn-Kellenberger, Oliver; et al.
Abstract : Background: RPTR-147 is a novel autologous non-genetically modified multi-clonal T cell product loaded with an IL15-Fc nanogel. The product was derived from rare peripherally-derived anti-tumor T cell clones that were primed against a multi-antigen cassette containing tumor associated antigens (TAA), known to be over-expressed in specific tumor types. We describe preliminary results from the ongoing first-in-human Phase 1 trial. Methods: Autologous anti-TAA T cells are generated with a proprietary dendritic cell priming process and then loaded with an IL15-Fc nanogel. TAAs used in cassette: PRAME, NY-ESO-1, SSX2, Survivin and WT1. Thawed RPTR-147 is delivered by infusion. Pre- and post-treatment biopsies were collected for biomarker analysis by immunohistochemistry (IHC) and transcriptome sequencing. Serial blood collections were obtained for measuring IL-15 pharmacokinetics and pharmacodynamic parameters including plasma cytokine levels and immunophenotyping by flow cytometry. T cell receptor sequencing (TCRSeq) was used to characterize the T cell repertoire from manufactured T cell product and the patient's blood. Results: Interim clinical and biomarker data from 17 patients with advanced metastatic disease refractory to SOC who received monthly infusions of 20-360 million cells/m², were reviewed (table 1). There were no dose-limiting toxicities and no evidence of cytokine-release syndrome. The 360M/m² dose contained 3X more IL15-Fc than the MTD of systemically administered IL15-Fc, 1 but produced less than a tenth of the systemic exposure to free IL15-Fc. Currently, 360M cells/m² is considered safe and well-tolerated. Further dose escalation is planned. Matched evaluable biopsies were obtained in 7 patients. Tumor-infiltrating T cell lymphocytes was observed in 5 cases for CD8 T cells and 4 cases for CD4 T cells. A dose dependent increase in both inflammatory cytokines and NK & CD8+ T cells was observed, consistent with expected MOA and PK. TCRSeq analysis demonstrated that product specific T cell clones could be tracked in both patient's blood and tumor over time. Further analysis to decode the specificity of those cells and demonstrate that tumor antigen specific T cells can be found in patient's blood and tumor biopsies is ongoing. Of the 17 patients who received RPTR-147 infusions 10 were noted to have stable disease (SD) and in 4 patients SD lasted > 6 months. Conclusions: Interim results with RPTR-147 have shown it to be well-tolerated and have a favorable safety profile. Dose-escalation is proceeding. Ongoing biomarker analysis will inform future clinical strategies in matching patients to an optimized PRIME IL-15 T cell product. Trial Registration: NCT03815682 Ethics Approval: The study was approved by local institutional IRBs after acceptance of the IND by the FDA. Consent: Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal. Reference: Romee R, Cooley S, Berrien-Elliott MM, et al. First-in-human phase 1 clinical study of the IL-15 superagonist complex ALT-803 to treat relapse after transplantation. Blood 2018;131(23):2515-2527.